Prospecção e atividade de actinobactérias de solo e de rizosfera de plantas da caatinga para controle do Colletotrichum musae (Berk. & M.A. Curtis) Arx - Ootani, Marcio Akio (2016)
Banana is one of the most consumed fruits in the country, economically important for Brazilian agriculture. However, production has been limited mainly by diseases in the field and post-harvest losses caused by fungi, including anthracnose, caused by Colletotrichum musae. The most recommended treatment for the control of this disease is the use of synthetic fungicides, which leave residues in the fruit and can lead to resistance of the pathogen. The use of antagonistic microorganisms and their metabolites may be a viable option for the control of the disease. Among these microorganisms the actinobacteria can be considered an alternative, due to the already known production of bioactive metabolites of the group. Studies on the antagonistic action of actinobacteria isolated from soil and rhizosphere of plants of the Caatinga biome are still scarce. This work aimed to prospect and isolate actinobacteria from the soil and the rhizospheric region of Caatinga plants, as well as to test the crude extract of bioactive isolates of these representatives of this group against C. musae, anthracnose agent in banana fruits. To obtain the actinobacteria isolates, the soil samples were submitted to pre-treatments with heat in comparison with the ambient temperatures, also with phenol in five concentrations. These tests were performed in different selective media, with four replicates. Subsequently, the effect of light on the number and diversity of actinobacterial colonies was evaluated. After this test it was concluded that the photoperiod increases the development of isolated actinobacteria colonies. As for the antagonism of the isolates obtained in relation to C. musae, metabolic activity was observed based on minimum inhibition concentration (MIC) and minimum fungicidal concentration (MFC). For the in vivo antagonism test against the banana anthracnose agent, crude extract of the actinobacteria isolates that were most active in the colony pairing test were tested, one of them being selected for its greater antagonism, it was then tested in different Concentrations and forms and time of application. It was concluded that the best concentration of the selected metabolite for the control of C. musae was 100 mg.ml-1, when applied to the surface of the fruit about 1 hour and 30 minutes before the pathogen. Therefore, of the more than 300 isolates obtained, only one had its metabolite effectively active in the antagonism to the target fungus, which is identified as Streptomyces showdoensis.